Limitaciones del enfoque de gestión estratégica en el sector público - Franco, Fabricio (2016)
This article examines the limitations that strategic management has had in the public sector to improve the performance and promote results in various state organizations. The problem is beyond the difficulties to measure the performance and identify results with impartiality in the public sector; rather, it is associated with a weak vision about the nature of the “public” sphere, and with how public policies are implemented in government organizations. The characteristics of the conventional approach in strategic management are presented, and the problems of importing acritically the private sector model without recognizing the political character of public organizations and their context, along with the public policy framework in which its results are inscribed, are analyzed. Likewise, the article claims that the implementation of their strategies happens in the organizational network context, and that the distinction between formulation and execution is not always clear.